PENINGKATAN KESEJAHTERAAN MASYARAKAT PETANI MELALUI PROGRAM UPSUS PAJALE DI LAMPUNG SELATAN - Khansa, Khodijah; Mukmin, Hasan; Yanti, Fitri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
The Ministry of Agriculture has formulated a policy to achieve food security in Indonesia, namely the Upsus PAJALE Program (special efforts for rice, corn and soybeans). Through this program, it is expected to be able to realize food security and improve the welfare of farmers. This study aims to reveal about: community empowerment activities of farmers and farmer welfare after participating in the Upsus PAJALE Program in South Lampung, especially Way Galih Village. The type of research used is field research with a qualitative descriptive approach. Data sourced from primary data and secondary data, with data collection techniques interview, observation, documentation, and data analysis by collecting data, data reduction, data presentation, data validity and conclusions. The results showed that the Upsus PAJALE Program had been carried out with various empowerment activities, namely: pre-planting to post-harvest assistance, training, providing farmers’ production tools and facilities, developing technology, developing partnerships, and developing marketing information. But what needs to be emphasized again is the marketing process, farmers are not given a guarantee of selling prices and there is no place to coordinate their harvests, so the government seems to only focus on increasing their production. Meanwhile, the welfare of farmers after participating in the Upsus PAJALE Program are: increasing productive land, increasing production yields, increasing farmer members, increasing knowledge, providing employment opportunities, and improving the farmer’s economy so that farmers become prosperous.